Factorial structure of physical rehabilitation group students’ complex fitness - I.N. Sobko; L.A. Ulaeva; Y.A. Yakovenko (Physical Education of Students)
Purpose: differentiation of physical education process on the base of morphological-functional state and physical fitness indicators, psycho-physiological potentials of physical rehabilitation group’s students. Material: 50 1st year students of 17-18 years’ age participated in the research. Tests for assessment of students’ morphological-functional state were used. Psycho-physiological testing was carried out with the help of computer program. Results: we marked out 5 factors, which characterize main components of students’ physical condition. It was determined that low level of students’ physical and functional potentials weakens functioning of organism’s most important functions. It was found that the most important factors in complex fitness of physical rehabilitation group’s students are power and functional potentials. Conclusions: it is necessary to purposefully work on formation of students’ comprehensive motor potential. Results of the research permit to rationally distribute physical education means and methods in practical trainings of physical rehabilitation group.